(3OjhGf Pj GdQeIs - (3ZjdGf Hf YbHI Hf fgjS Hf eSYhO GdYOhj, ef eVQ, CHh GdMGQK, Ph GdQeI,J (B117 (3g` s
(3ChdgG (B:s
(3hbGd Ph GdQeI CjVkG(B: s
(3BNQgG (B:s
(3HMhQ hMcGe bVGI hPGOI EPG UGQ CbhGe ShGce ehGdjG Je TYQ Pj GdQeI HCSQg s
(3YdjgG JedjcGJ aj GdbQf GdSGHYs
(3QhGjI GdCUeYj hZjQgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B319 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B44s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B105 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B789s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs